Comprehensive performance prediction and power promotion for wearable thermoelectric generator with flexible encapsulation in practical application. (15th September 2020) - Liu, Youhong; Shi, Yaoguang; Li, Jing; Guo, Xiaofeng; Wang, Yancheng; Xiang, Qingpei; Guo, Simao; Ze, Rende; Zeng, Jun; Xiang, Yongchun; Hao, Fanhua
Highlights: A comprehensive FEM model of the WTEG with encapsulation in practice is realized. Calculation results are validated by experiment with average error less than 4.2%. The effects of side heat loss on temperature and voltage distribution are studied. Impacts of geometric and material parameters on the performance are investigated. The power of optimal WTEG with matched loading resistance is improved by 598.1%. Abstract: With ability of converting the heat harvested from human body into electricity, the wearable thermoelectric generators (WTEGs) are attracting lots of interests for self-powered electronic devices. However, the output power density of the WTEG is limited for supplying the electronic devices. Therefore, the performance enhancement by optimal design of the developed WTEGs is needed. In this paper, a method of comprehensive modeling of a WTEG is proposed by considering all essential components and realistic boundary conditions. By solving the model with finite element modeling (FEM) method, the calculation performances agree well with experimental results at various temperature difference and load resistance. Through the temperature and voltage distribution of the WTEG obtained, the effects of side heat loss and heat conduction of the encapsulation are revealed. Besides, the impact of the thermal conductivity of encapsulation and the geometric dimensions of thermoelectric legs on the output performance are explored. Finally, the performance prediction results indicate that at the temperature difference of 15 K, the output power of the WTEG with optimized design can be improved about 598.1% with matched loading resistance compared to the device with original design.